2020
DOI: 10.1186/s12905-020-00948-0
|View full text |Cite
|
Sign up to set email alerts
|

The association between labor epidural analgesia and postpartum depression: a systematic review and meta-analysis

Abstract: Background: Previous studies have demonstrated that appropriate treatment for postoperative pain can lead to improvement in depressive symptoms, however the association between adequate intrapartum pain control and the development of postpartum depression is not clear. The purpose of the study was to examine the effects of labor epidural analgesia and postpartum depression. Methods: We performed a quantitative systematic review in compliance with the PRISMA statement. We conducted a search of PubMed, Embase, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
12
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 34 publications
(20 reference statements)
3
12
1
1
Order By: Relevance
“…The results of statistical tests obtained a p-value of <0.05. Thus, it can be concluded that there is a significant relationship between physical exercise and postpartum depression (Almeida et al, 2020). This is in line with the literature that the lack of family support, especially from husbands and other close family members can trigger postpartum depression (Rosenthal & Henderson, 2003;Wolwan, 1993cit Hutagaol, 2010.…”
Section: Discussionsupporting
confidence: 75%
“…The results of statistical tests obtained a p-value of <0.05. Thus, it can be concluded that there is a significant relationship between physical exercise and postpartum depression (Almeida et al, 2020). This is in line with the literature that the lack of family support, especially from husbands and other close family members can trigger postpartum depression (Rosenthal & Henderson, 2003;Wolwan, 1993cit Hutagaol, 2010.…”
Section: Discussionsupporting
confidence: 75%
“…It is intriguing that not receiving the desired medication was associated with increased depressive symptoms in the postpartum period. While epidural anesthesia during labor is neither a risk factor nor a protective factor against postpartum depression [45][46][47], unmatched expectations of medications during labor have been demonstrated to result in higher rates of postpartum depression [48,49]. Relative risk of postpartum depression appears to be higher both for those who intended to deliver with epidural anesthesia during labor, but did not receive it [49], as well as those who intended not to deliver with epidural anesthesia but ultimately received it [48,49].…”
Section: Discussionmentioning
confidence: 99%
“…Aggregated effect of the studies that investigated PPD among women who received epidural analgesia compared to controls found no significant differences (OR 1.02, 95% CI, 0.62–1.66). 19 Overall, this meta-analysis showed a lack of association between the use of epidural analgesia and postpartum depression. These observational studies cannot account for unknown confounders, which can only be adequately managed by randomized clinical trials.…”
Section: Results/data Analysismentioning
confidence: 75%